Pollen morphology in selected species of Caricaceae with special reference to novel palynological characters - Zini, Lucia Melisa (2018)
The pollen grain morphology of Jacaratia corumbensis Kuntze, J. spinosa (Aubl.) A.DC., Vasconcellea quercifolia A. St.-Hil., and Carica papaya L. from Argentine samples were examined for the first time, using light and scanning electron microscopes. Observations and measurements were performed on acetolyzed pollen grains. Principal-components analysis was performed for quantitative morphological variables. Pollen grains were tri-colporate with lalongate endoaperture, oblate spheroidal to prolate, medium, exine bireticulate or reticulate, with a granulate lumina. A fastigium was present. Novel palynological data in this study for species identification revealed the presence of margo in C. papaya and variations in endoaperture shapes in all the species. The endoaperture ends often were H-shaped or horn-shaped. A biplot showed clear separation of the four taxa based on the palynological traits. Vasconcellea quercifolia was strongly correlated with equatorial diameter, equatorial diameter in polar view, exine thickness, and polar diameter, whereas J. corumbensis and J. spinosa were positively correlated with polar index and polar area index, respectively. The distance between two colpi allowed the discrimination of C. papaya. We confirmed the homogenous nature for most of the qualitative palynological characters in Caricaceae, and demonstrated that pollen morphology in combination with statistical analyses is a reliable tool for delimiting taxonomic groups.